The use of constructed-response testing in nursing education. - Kelly AL (Use of Constructed-response Testing in Nursing Education, 1998)
Undergraduate nursing students are primarily tested by multiple choice instruments that employ decontextualized, situational settings. This type of testing is used because the licensing examination in nursing is a multiple choice test. Other disciplines such as mathematics and science are now using alternative assessment formats which better demonstrate student knowledge and thought.This qualitative study was designed to examine the utility of constructed response, modified essay testing in which questions are asked in a richer, more true to life context. Test questions were created in a content area of neurological care and were given at the same time as a multiple choice examination of the same content to a pilot study group of senior nursing students at a community college. A preliminary analysis of the responses to the items was conducted and questions were modified to create a better match of content on the two test types and to elimination confusions of wording.The dissertation study was completed using 27 students at the same community college school of nursing. Student responses to both types of questions were examined for understanding of knowledge and the ability to use the knowledge in a simulated clinical setting. Students were also interviewed about their preferences for different test types.Constructed response and multiple choice test scores of the same content showed no correlation. The researcher found that nursing students answer multiple choice questions by recall and when recall fails, they contextualize questions to find an answer or they apply a complex decoding algorithm to find a correct answer. Content answered correctly on the multiple choice test is often incomplete when questioned on the constructed response items. Constructed response items demonstrate lack of ability to think critically in a clinical situation, and show that misconceptions are held by even the best students. Neither test type provides a complete description of student knowledge and neither should be used to rank a student in class or to assert that a student is fluent in the subject matter.